Regulatory T cells with multiple suppressive and potentially pro-tumor activities accumulate in human colorectal cancer. (2nd July 2016) - Timperi, Eleonora; Pacella, Ilenia; Schinzari, Valeria; Focaccetti, Chiara; Sacco, Luca; Farelli, Francesco; Caronna, Roberto; Del Bene, Gabriella; Longo, Flavia; Ciardi, Antonio; Morelli, Sergio; Vestri, Anna Rita; et al.
ABSTRACT: Tregs can contribute to tumor progression by suppressing antitumor immunity. Exceptionally, in human colorectal cancer (CRC), Tregs are thought to exert beneficial roles in controlling pro-tumor chronic inflammation. The goal of our study was to characterize CRC-infiltrating Tregs at multiple levels, by phenotypical, molecular and functional evaluation of Tregs from the tumor site, compared to non-tumoral mucosa and peripheral blood of CRC patients. The frequency of Tregs was higher in mucosa than in blood, and further significantly increased in tumor. Ex vivo, those Tregs suppressed the proliferation of tumor-infiltrating CD8 + and CD4 + T cells. A differential compartmentalization was detected between Helios high and Helios low Treg subsets (thymus-derived versus peripherally induced): while Helios low Tregs were enriched in both sites, only Helios high Tregs accumulated significantly and specifically in tumors, displayed a highly demethylated TSDR region and contained high proportions of cells expressing CD39 and OX40, markers of activation and suppression. Besides the suppression of T cells, Tregs may contribute to CRC progression also through releasing IL-17, or differentiating into Tfr cells that potentially antagonize a protective Tfh response, events that were both detected in tumor-associated Tregs. Overall, our data indicate that Treg accumulation may contribute through multiple mechanisms to CRC establishment and progression.